Improving teaching and learning in systems programming courses using participatory action research - Delgado, Alexi (2016)
One of research areas of Systems Engineering is software development; for which, high level of programming using different languages is required. Therefore, students have basic, intermediate, and advanced programming courses, within their curriculum; currently these courses have a high rate of disapproval. In this article, we develop a case study on the programming course of systems engineering degree from the University of Sciences and Humanities, Peru. Following the stages of participatory action research methodology. First, a diagnosis was made, in which a rate of disapproval of 58% was identified. Second, a technique of participatory teaching and learning, using previous materials and exams, was applied. Third, results were measured, in which the rate of disapproval was reduced to 8%. Additionally, results revealed that 82% of participants opined that improved their learning, 75% that decreased the degree of anxiety, 92% that improved the relationship with their teacher, 100% that increased the motivation toward a new evaluation, as they previously knew the subject and the evaluations difficulty of the course.